PROFILE OF STUDENT MATHEMATICAL CONNECTION ABILITIES IN UNDERSTANDING MATHEMATICAL CONCEPTS IN TERMS OF GENDER - Amalia Fitria Ningsih; Lilik Ariyanto; Ida Dwijayanti (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2018)
According to Permendikbud number 58 in 2014, one of the objectives of learning mathematics is to be able to understand mathematical concepts. In understanding mathematical concepts, of course, students need mathematical connection skills to connect between concepts and real life. There are many differences between men and women, especially ways of thinking, perspective, and mathematical abilities. For this reason researchers want to know how the profile of students' mathematical counseling ability in understanding mathematical concepts in terms of gender. This study aims to determine the profile of students' mathematical connection abilities in understanding mathematical concepts in terms of gender. This research is a qualitative descriptive study. The research subjects were 3 male students and 3 female students of class VII MTs N 1 Kudus who were selected based on the daily score of the medium group. Data collection techniques in the form of written tests and interviews. The validity of the data uses source triangulation. The results of this study are: a) Profile of male students' mathematical connection ability in understanding mathematical concepts that is at the stage of interpreting, male students interpret by looking at the length of their sides. At the stage of imitating by looking around objects. In the classifying stage by looking at the number of sides. At the stage summarize by remembering what is in the book and see the shape. At the stage of concluding, connect with the characteristics. At the comparing stage, by looking at the sides and corners, but unable to relate to other material. At the explaining stage, with your own thoughts by looking at the shape. b) Profile of female students' mathematical connection abilities in understanding mathematical concepts that is at the stage of interpreting, female students interpret images because of their desires. At the example stage, by looking around objects. In the classifying stage, only mention the name of the object. At the stage of summarizing, remembering what is in the book and what the teacher teaches. At the stage of concluding, connect with the characteristics. At the comparing stage, by looking at sides and angles and also linking with other material. At the explaining stage, remember what is in the book